DEVELOPMENT OF DIGITAL FLIPBOOK TRAINING MEDIA FOR SWEET BREAD VARIATIONS - Yudhawarman, Anisah Aulia; Artanti, Guspri Devi; Kandriasari, Annis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to develop digital flipbook training media for sweetbread variations that can be used as learning media for bakery training programs, as well as to analyze the feasibility of the digital flipbook training media for sweetbread variations developed. This media was developed using the research and development (RD) method and adapting the ADDIE development model. The development steps of this research are as follows: 1) Analysis; 2) Design; 3) Development; 4) Implementation; and 5) Evaluation. This training media has gone through a validation process carried out by material experts, media experts, and also linguists. Validation tests conducted by material experts obtained results of 96% with very good qualifications, 93% for linguists with very good qualifications and 89% for media experts with good qualifications. At the training participant test stage, a one-on-one test was carried out on 3 participants, a small group test was conducted on 8 people, and a field group test was carried out on 15 people. In the one-on-one test, 84% of the results obtained with good qualifications needed revision, 89% of the small group assessment results with good qualifications needed revision, and 90% of the group's assessment results were very good. qualification. The conclusion shows that the digital flipbook training medium for the sweet bread variation can be well received by users when used as a training medium.